SENIMAN DAN SENI PERTUNJUKAN DI KAMPUNG KEMLAYAN SURAKARTA 1930-1970 - Heri Priyatmoko (Jantra., 2019)
This research departs from the assumption that generally the public only comprehend artists only when they appear on stage, They do not realize their creative activities while they are staying at home. The focus of this research is the community of gamelan musicians and dancers who settled in kampong Kemlayan, Surakarta from 1930-1970. The method used in this study is the historical method including heuristics, source verification, interpretation, and historiography. The results of the research showed that the palace artists in Kasunanan Surakarta considered that the kampong where they live was not only a place to live but also a place where they can practice and rehearse before they performed in the palace in front of their King or in other public spaces. It is in their small kampong that they cultivate creativity without strict rules like in the palace. New gendhings (gamelan songs) and choreographies were born in this kampong. This had strengthened the kampong’s identity as the “breeder” of productive artists. For decades, lots of karawitan and dance activities in Kemlayan had changed its face. It was like a “stage” that invited the people’s and local children’s attention. The plenty activities had attracted and encouraged the local children to join the activities. In this way, regeneration process was taking place.